Radial artery thrombosis following transradial coronary angiography: incidence and rationale for treatment of symptomatic patients with low-molecular-weight heparins - Zankl, Alexandra R.; Andrassy, Martin; Volz, Hans Christian; Ivandic, Boris; Krumsdorf, Ulrike; Katus, Hugo; Blessing, Erwin (Clinical research in cardiology, 2010)
Transradial access for diagnostic and therapeutic coronary angiography gains more and more popularity because of its advantages over the femoral approach, enhancing patient comfort, reducing bleeding complications and duration of hospital stay. However, these benefits are overshadowed by an increased rate of radial artery (RA) occlusion. There are little data regarding the exact incidence, potential predictors and outcome of post-procedural RA occlusions. Furthermore, there is no clear evidence for the optimal treatment of this complication.
Published: 13 July 2010
Gesehen am 17.04.2024